2017
DOI: 10.5005/jp-journals-10028-1221
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Ex-PRESS and Trabeculectomy in a Glaucoma Population of African Origin: One Year Results

Abstract: Aim To compare the efficacy and safety of Ex-PRESS glaucoma filtration surgery to trabeculectomy in African origin patients.Materials and methods A retrospective chart review was performed on 56 African American patients undergoing Ex-PRESS glaucoma shunt (E) or trabeculectomy (T) between 2004 and 2012. Data collected included intraocular pressure (IOP) and glaucoma medication use at baseline and postoperative week 1, Month (M) 1, M3, M6, M12. Postoperative interventions including laser suture lysis (LSL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…1 Despite the potential reduction of IOP following trabeculectomy with the use of antimetabolites, several visionthreatening complications may still occur, such as hypotony maculopathy, choroidal effusion, suprachoroidal hemorrhage, and bleb-related endophthalmitis. 1,2 The XEN gel implant, a hydrophilic, non-inflammatory, subconjunctival gelatin stent (XEN Gel Stent, Allergan, Dublin, USA), provides an ab interno approach to create a permanent channel from the anterior chamber to the subconjunctival space and is designed to avoid early postoperative hypotony. 3,4 The flexibility of the implant and its expansion upon hydration allow it to be tissue conforming and thus preventing the risk of extrusion and migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Despite the potential reduction of IOP following trabeculectomy with the use of antimetabolites, several visionthreatening complications may still occur, such as hypotony maculopathy, choroidal effusion, suprachoroidal hemorrhage, and bleb-related endophthalmitis. 1,2 The XEN gel implant, a hydrophilic, non-inflammatory, subconjunctival gelatin stent (XEN Gel Stent, Allergan, Dublin, USA), provides an ab interno approach to create a permanent channel from the anterior chamber to the subconjunctival space and is designed to avoid early postoperative hypotony. 3,4 The flexibility of the implant and its expansion upon hydration allow it to be tissue conforming and thus preventing the risk of extrusion and migration.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite the potential reduction of IOP following trabeculectomy with the use of antimetabolites, several vision-threatening complications may still occur, such as hypotony maculopathy, choroidal effusion, suprachoroidal hemorrhage, and bleb-related endophthalmitis. 1,2…”
Section: Introductionmentioning
confidence: 99%
“…Regarding corneal endothelial cells, some studies have proven their safety [ 12 , 13 , 26 , 27 , 28 ]. Previous studies reported no significantly faster loss in endothelial cell counts after Ex-PRESS implantation compared with trabeculectomy [ 14 , 17 , 29 ]. While other studies reported that corneal endothelial cell density (CECD) was significantly decreased after Ex-PRESS implantation [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 88%
“…Compared with trabeculectomy, it has the advantages of reduced trauma, simple operation, and improved safety. Most studies proved that the Ex-PRESS implantation had an equivalent curative effect to trabeculectomy [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], even with more complete success [ 21 , 22 ]; however, some literature argued that it was less effective than trabeculectomy [ 23 , 24 , 25 ]. Regarding corneal endothelial cells, some studies have proven their safety [ 12 , 13 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in the case of neovascular glaucoma, standard trabeculectomy proved better performances as compared to Ex-PRESS. Ex-PRESS shunt interventions differ from one study to another, in terms of what and how frequently, but all patients received mitomycin C as anti-mitotic medication (Table I) [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%